Validity and Internal Consistency of the Thai Version of a Revised Skin Management Needs Assessment Checklist in People with Spinal Cord Injury: Initial psychometric studies - Soonthornthum, Chutimon; Prommueang, Paksupa; Tongprasert, Siam (Biomedical Sciences and Clinical Medicine, 2025)
OBJECTIVE This study aims to cross-culturally translate the revised Skin Management Needs Assessment Checklist (revised SMnac) into Thai (revised SMnac-TH), to evaluate its content validity and internal consistency and to determine the relationship between the revised SMnac-TH score and the occurrence of pressure injuries. METHODS The study design is a descriptive cross-sectional study. It was conducted at the Inpatient and Outpatient Rehabilitation Medicine Department of Maharaj Nakorn Chiang Mai Hospital, involving one hundred twenty-five Thai people age > 18 years old with spinal cord injury. The French version of the revised SMnac was translated into Thai following the standard guidelines for translation and cross-cultural adaptation. The content validity was evaluated by six experts in rehabilitation medicine. Each of the participants completed the revised SMnac-TH. The internal consistency was measured using Cronbach’s alpha coefficient. Logistic regression analysis was used to evaluate the relationship between the revised SMnac-TH score and the occurrence of pressure injuries. RESULTS The index of item-objective congruence (IOC) of each item ranged from 0.83-1.00. The Cronbach’s alpha coefficient of the questionnaire was 0.923. The logistic regression analysis showed no correlation between the revised SMnac-TH score and the occurrence of pressure injuries. CONCLUSIONS The revised SMnac-TH demonstrated high content validity and internal consistency. It proves to be a useful tool for evaluating pressure injury-related knowledge and skin protective behaviors among Thai individuals with spinal cord injury. KEYWORDS pressure injury, spinal cord injury, patient education